Breast cancer in pregnancy - case report - Jovanova Daniela; Kochoski, Goran; Selami A (SHMSHM / AAMD, 2013)
Breast cancer in pregnancy (BCP) is relatively rare with an incidence of 1:3000 to 1:10 000 births. Breast cancer in pregnancy is second most frequent among malignancies in pregnancy, right behind cervical cancer. The diagnosis of BCP is made if the condition appears during the pregnancy, or during the first year after delivery, with some variations in duration of the postnatal period that is taken into consideration, varying from 6 months to 2 years. Most of the tumors are adenocarcinomas, scirus, colloid or anaplastic. As in all cases of breast cancer outside pregnancy, biopsy is a "gold standard" in the diagnosis of this condition during pregnancy. Imaging diagnostic techniques have limited application either because of the increased false positive rate or lower sensitivity. Pregnancy termination does not represent an efficient therapeutic alternative. Surgical treatment is a supreme therapeutic procedure in the treatment of BCP. In patients that have been diagnosed during the late second trimester, optimal treatment comprises of dissection of the tumor mass and axillar lymph nodes, followed by delivery and radiation therapy. We are presenting a case of 34 years old patient with poorly differentiated breast carcinoma, Stage IIIC, during the late second trimester. After the surgery the delivery was postponed until 37th week. Through presentation of this case we've tried to show that there is an open possibility to postpone the delivery in patients in which the diagnosis was made in the late second trimester, for until the late third trimester or even until the EDD, and yet not to compromise overall prognosis of the patient.
Keywords: breast cancer; pregnancy; biopsy; delivery; radiation therapy